2017
DOI: 10.18632/oncotarget.15185
|View full text |Cite
|
Sign up to set email alerts
|

OIP5, a target of miR-15b-5p, regulates hepatocellular carcinoma growth and metastasis through the AKT/mTORC1 and β-catenin signaling pathways

Abstract: Opa interacting protein 5 (OIP5) is upregulated in some types of human cancers, but the biological implications of its upregulation have not yet been clarified in human hepatocellular carcinoma (HCC). In this study, the signaling pathway downstream of OIP5 was analyzed by proteome kinase profiling. A putative microRNA targeting OIP5 was identified using a miRNA PCR array. Tumorigenicity and metastatic ability were examined in an orthotopic animal model. OIP5 expression was strongly detected in early and advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…miR-15b-5p was found down-regulated in HCC cells and OIP5 was found to be its direct target. These findings suggest that the restoration of miR-15b-5p could inhibit OIP5-mediated oncogenic signaling in HCC[ 33 ].…”
Section: Mirnas In Hcc Molecular Pathwaysmentioning
confidence: 99%
“…miR-15b-5p was found down-regulated in HCC cells and OIP5 was found to be its direct target. These findings suggest that the restoration of miR-15b-5p could inhibit OIP5-mediated oncogenic signaling in HCC[ 33 ].…”
Section: Mirnas In Hcc Molecular Pathwaysmentioning
confidence: 99%
“…Investigation of the mechanisms underlying the regulation of breast cancer by miRNAs is essential (9). The miRNA miR-15b-5p, a mature miRNA which is spliced from the 5 ′ -end of pre-miR-15b (10), has been reported to be expressed in many cancers, including gastric cancer (11), colorectal cancer (12), prostate cancer (13), bladder cancer (14), and hepatocellular carcinoma (15). In these tumors, miR-15b-5p promotes proliferation, decreases apoptosis, induces tumor metastasis and recurrence, and is associated with poor patient prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that miR-212 suppresses tumor growth of HCC by targeting forkhead box protein A1 (FOXA1) [ 7 ]. And miR-15b-5p regulates HCC growth and metastasis through the AKT/mTORC1 and β-catenin signaling pathways [ 8 ]. Recently, Liu C et al reported that miR-324-3p could modulate cancer cell growth and apoptosis by targeting SMAD family member 7 (SMAD7) in nasopharyngeal carcinoma [ 9 ].…”
Section: Introductionmentioning
confidence: 99%